Extracellular matrix biomimetic polymeric membranes enriched with silver nanoparticles for wound healing. (1st March 2021) - Stefan, Laura Mihaela; Iosageanu, Andreea; Ilie, Daniela; Stanciuc, Ana-Maria; Matei, Cristian; Berger, Daniela; Craciunescu, Oana
Abstract: Severe skin injuries, including burns, represent a real concern for the global health-care system and therefore, there is an increased interest in developing wound dressings, in order to stimulate and enhance skin tissue repair. The aim of this study was to design novel hybrid materials, biomimetic to skin extracellular matrix and enriched with silver nanoparticles (nAg), in order to provide both dermal tissue regeneration and antimicrobial activity. Two material variants (variant A and variant B) consisting of type I collagen (COL), chondroitin sulfate (CS) and k-elastin peptides (EL) enriched with positively-charged nAg, were conditioned as membranes. UV exposure ensured both sterilisation and cross-linking of the materials. Physico-chemical characterization of the hybrid biomaterials showed values of density and swelling degree higher than those of COL membrane, while the process of in vitro degradation followed a similar pattern. Infrared spectroscopy and x-ray diffraction indicated alterations of the characteristic structural features and crystallinity of COL after blending with CS and EL and nAg embedding. Scanning electron microscopy observations revealed different surface morphologies of the hybrid membranes, according to their composition. In vitro studies on L929 fibroblasts and HaCaT keratinocytes showed that both hybrid membranes exhibited good cytocompatibility and promoted higher cell proliferation compared to COL sample, as evaluated by MTT and Live/Dead assays. The presence of actin filaments highlighted by fluorescent labelling confirmed the fibroblast and keratinocyte adhesion onto the surface of hybrid membranes. Most importantly, both materials showed an increased wound healing ability in an in vitro scratch assay model, stimulating cell migration at 24 h post-seeding. In addition, good antimicrobial activity was recorded, especially against Gram-positive bacterial strain. Altogether, our findings recommend COL-CS-EL-nAg hybrid membranes as good candidates for wound healing acceleration and bioengineering of skin tissue.